Loudermilk, or, The real poet, or, The origin of the world : a novel - Ives, Lucy, 1980- (Soft Skull, 2019)
"It's the end of summer, 2003. George W. Bush has recently declared the mission in Iraq accomplished and the unemployment rate is at its highest level in years. Meanwhile, somewhere in the Midwest, Troy Augustus Loudermilk (fair-haired, statuesque, charismatic) and his companion Harry Rego (definitely none of those things) step out of a silver Land Cruiser and onto the campus of The Seminars, America's most prestigious creative writing program, to which Loudermilk has recently been accepted for his excellence in poetry. However, Loudermilk has never written a poem in his life. For all Troy Loudermilk is--and, in the eyes of his fellow students and instructors, he is many things: a cipher to be solved, a hero to be championed, a rival to be disgraced--a poet he most certainly is not. Wonderfully sly and wickedly entertaining, Loudermilk is a social novel for our times--a subversive look at the pieties of contemporary literature and the institutions that sustain them" --